4X6 POSTER STRATEGY TOWARDS STUDENTS’ CREATIVITY AND THEIR MASTERY IN WRITING AT FPBS IKIP MATARAM - Hasby, Muhammad Asrul; S., Komang Dedy Sandiarsa (Jurnal Ilmiah IKIP Mataram, 2018)
This research was aimed 1) To find the diferences between students having high creativity and students having low creativity, 2) To indentify the interaction between studentsâ€™ creativity and 4x6 poster strategy in their writing mastery. The research was quasi experimental. In this research, represented factorial 2X2 Analysis of Variant (ANOVA) design. Next to that, this research deal with the third semester of English department program with the total number was 80 students in which it was assumed that they have not creative in writing. Next to that, the data collected by using verbal creativity test and questionnare. The techniques of data analysis was used descriptive analysis and inferential analysis. In analyzing data of the research the researcher used tâ€“test formula. Based on the analysis, it was gotten that t-test score was 2.58 with the degree of freedom (df) = 78 and t-table was 2.00 at the significant level =0.05 It means that the value of t-test was bigger than t-table. Alternative hypothesis is accepted (Ha) and Null hypothesis (Ho) is rejected. In conclusion, There is a significant effect of 4x6 poster strategies towards students’ cretivityÂ at FPBS IKIP Mataram